Sex differences in predictability of some measures of college achievement from the college entrance test and/or some measures of high school achievement - Gumban, Remigio S. ([Metro Manila] Psychological Association of the Philippines, 1972)
Tests of significance of the hypotheses that the predictabilities of college academic criteria (viz., subject-area averages in English, Mathematics, and Social Science, and; an overall measure, defined as average of the subject-area measures) arc equal for male and female "populations" of college freshmen are presented. The findings are as follows: (1) Non-significant sex differences in predictability of the college overall measure, and subject-area average in Social Science when predicted from (a) high school subject-area averages, (b) CET subtest scores, (c) combination of the high school and CET variables, and (d) overall measures in high school (i.e., average of the subject-area averages) and the CET; (2) Significant sex differences in predictabilities of subject-area average in Mathematics in all four prediction schemes above; (3) Significant sex differences in predictability of subject- area average in English in three prediction schemes, viz., (b)-(d) above. Discussions on (1) the "fidelity" of single measures of initial college academic performance, and (2) the implications of the results for admissions purposes arc also presented.
Includes bibliographical references (page 48)
Keywords: Psychology Philippines -- Periodicals